Tatonnement Stability of Infinite Horizon Models with Saddle-Point Instability - Heller, Walter Perrin (Econometrica, 1975)
Consider a competitive economy with infinite horizon Ramsey behavior by households, present-value maximizing firms and infinitely many futures markets. If prices adjust according to excess demands, then the economy is locally stable. This is in marked contrast to the saddle-point instability exhibited by the myopic foresight dynamics in models of this genre. It is argued that infinite futures markets are idealizations of actual economic forces.